2010
DOI: 10.1002/ppul.21333
|View full text |Cite
|
Sign up to set email alerts
|

Nasal potential measurements on the nasal floor and under the inferior turbinate: Does it matter?

Abstract: NPD measurements under the inferior turbinate and on the nasal floor have similar discriminative power for diagnostic use. Measurements under the turbinate result in a slightly higher proportion of interpretable tracings but sample size calculation slightly favors the nasal floor method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…Finally, testing the same subjects on different days with warmed or room temperature solutions showed differences of -15-20 mV in total chloride response, probably reflecting day-to-day variability rather than the different temperatures tested. The differences observed are in line with previous studies of day-to-day variability [2,12].…”
Section: Discussionsupporting
confidence: 82%
“…Finally, testing the same subjects on different days with warmed or room temperature solutions showed differences of -15-20 mV in total chloride response, probably reflecting day-to-day variability rather than the different temperatures tested. The differences observed are in line with previous studies of day-to-day variability [2,12].…”
Section: Discussionsupporting
confidence: 82%
“…NPD was measured with an end-hole Marquat® catheter under the IT instead of on the nasal floor, as suggested in the latest ECFS-NPD-SOP. Vermeulen et al demonstrated that measurements under the IT and the nasal floor have similar discriminative power for diagnostic use [16]. Therefore we believe this difference would not have changed our final conclusion.…”
Section: Discussionmentioning
confidence: 72%
“…We used 3 different criteria to discriminate between CF and non-CF, taking into account a total chloride response less than − 10 mV [12,15,16], and Sermet and Wilschanski composite scores as described in the original articles, being less than 0.27 for Ser score (developed with Abr method) and more than 0.7 for Wils score (developed with Ndl method) in the case of CF [17,18]. Previous papers have underlined the importance of taking into account the combined response on the different solutions, showing the ENaC-response on the Amilo solution and the net effect of chloride efflux due to passive (chloride-free solution) and active (cAMP-activated CFTR activity by isoproterenol) chloride transport [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other groups may measure the PD on the nasal floor, which is technically easier. Importantly, Vermeulen (2011) demonstrated that the 2 methods are comparable 16 .…”
Section: Modifications and Troubleshootingmentioning
confidence: 99%